Blockchain Technology as a Game Changer for Green Innovation: Green Entrepreneurship as a Roadmap to Green Economic Sustainability in Peru - Mohammad Rashed Hasan Polas; Ahmed Imran Kabir; Abu Saleh Md. Sohel-Uz-Zaman; Ridoan Karim; Mosab I. Tabash (Journal of Open Innovation: Technology, Market and Complexity, 2022)
Blockchain technology has been heralded as a game changer for addressing severe environmental and economic sustainability challenges. In response to rising environmental concerns, blockchain technology (BCT) is transforming green innovation, culminating in green economic practices and well-established business models. Recognizing this, we investigated the role of blockchain technology in green innovation practices and its impact on green economic sustainability, which has an impact on green environmental sustainability. Moreover, 184 small- and medium-sized enterprises (SMEs) were surveyed in Lima, Peru. Data for this cross-sectional study were gathered using stratified random sampling. The positivist approach was implemented using a statistical induction method. Prior studies’ research constructs were measured using validated measurement scales. For quantitative data analysis, using the partial least squares structural equation modeling (PLS-SEM) framework, this study provided two key findings. First, sustainability orientation and sustainability attitude have a positive and significant effect on the adoption of green innovation that employs green energy (solar) technology towards a sustainable green economy. Second, the intention to use blockchain technology mediates the relationship between sustainability orientation and social perception with the adoption of green innovation that employs green energy (solar) technology towards a sustainable green economy. We recommend that small- and medium-sized enterprises embrace green innovation and blockchain technology to protect the environment and boost community cohesiveness.